TRIM proteins in autophagy: selective sensors in cell damage and innate immune responses - Di Rienzo, Martina (Cell Death Differ, 2020)
Autophagy, a main intracellular catabolic process, is induced in response to a variety of cellular stresses to promptly degrade harmful agents and to coordinate the activity of prosurvival and prodeath processes in order to determine the fate of the injured cells. While the main components of the autophagy machinery are well characterized, the molecular mechanisms that confer selectivity to this process both in terms of stress detection and cargo engulfment have only been partly elucidated. Here, we discuss the emerging role played by the E3 ubiquitin ligases of the TRIM family in regulating autophagy in physiological and pathological conditions, such as inflammation, infection, tumorigenesis, and muscle atrophy. TRIM proteins employ different strategies to regulate the activity of the core autophagy machinery, acting either as scaffold proteins or via ubiquitin-mediated mechanisms. Moreover, they confer high selectivity to the autophagy-mediated degradation as described for the innate immune response, where TRIM proteins mediate both the engulfment of pathogens within autophagosomes and modulate the immune response by controlling the stability of signaling regulators. Importantly, the elucidation of the molecular mechanisms underlying the regulation of autophagy by TRIMs is providing important insights into how selective types of autophagy are altered under pathological conditions, as recently shown in cancer and muscular dystrophy.